Transcriptomics and iTRAQ-proteomics analyses provide novel insights into the defense mechanism of black shank disease in tobacco - Bai, Ge; Fang, Dun-Huang; Yang, Da-Hai; Tong, Zhi-Jun; Chen, Xue-Jun; Fei, Ming-Liang; Gong, Jiu-Ling; Xie, He; Xiao, Bing-Guang (Frontiers in Plant Science, 2022)
Black shank disease caused by Phytophthora nicotianae is one of the most important diseases in tobacco worldwide and can result in a devastating loss in tobacco cultivation. Many efforts have been carried out to identify the chromosome segment from Nicotiana plumbaginifolia containing a resistance locus carrying a gene named Php; however, the Php gene has not been cloned, and knowledge of the potential mechanism of the Php gene in the resistant lines is limited. To further characterize the resistance mechanism of the Php gene, we first used the resistant line ‘RBST’ and the susceptible cultivar ‘Honghuadajinyuan’ (HD) to obtain the near isogenic line RBS89 containing the Php gene from RBST. RBS89 showed high resistance to black shank disease. Transcriptomic and iTRAQ analyses were applied to explore the potential defense mechanisms in RBS89 plants in comparison with HD plants with or without inoculation. Many differentially expressed genes and proteins were identified, and some pathogenesis-related (PR) proteins were extensively abundant in the RBS89 plants when compared with the HD plants in response to black shank disease. Importantly, overexpression of the PR gene NtPR-1B in HD plants improved the resistance of tobacco plants to black shank disease, indicating that NtPR-1B and Php genes might have similar roles in protecting tobacco from black shank disease. However, the relationship between NtPR-1B and Php genes requires further analysis. Therefore, our study provides valuable information for breeding tobacco cultivars with black shank disease resistance and sheds light on the defense mechanism of black shank disease in tobacco for enhancing Phytophthora resistance in other Solanaceae crops.